THE EFFECT OF GIVING DELTAMETHRIN AND CYPERMETHRIN INSECTICIDES ON THE LEVEL OF INTRATESTICULAR TESTOSTERONE IN MALE WISTAR STRAIN RATS - Triutomo, Devyanto Hadi; Puspitasari, Ika; Susidarti, Ratna Asmah (Indonesian Journal of Pharmacy, 2020)
The use of deltamethrin and cypermethrin insecticides to control pests has been implemented in Indonesia. Irregular and excessive use of insecticides can have toxic effects on the male reproduction system. Deltamethrin and cypermethrin insecticides can inhibit androgen biosynthesis and disrupt the growth of sperm. Therefore, this research is conducted to find out the effect of deltamethrin and cypermethrin insecticides toward the level of intratesticular testosterone in male Wistar strain rats. This research is conducted in vivo using male Wistar strain rats. Nine rats are divided into three groups of treatment, namely control group, deltamethrin group with 0.26 mg/kg of weight, and cypermethrin group with 0.26 mg/kg of weight. Treatment is conducted every day for 15 days orally, and then the rats are dissected to take their testicles. Testicles are chopped and their intratesticular homogenates are taken by adding the medium of DMEM and collagenase (0.25 mg/mL). The measurement of the level of testosterone is conducted by using Electrochemiluminescence immunoassay (ECLIA) method. Data on the change of the increase of body weight, organ weight, and the level of testosterone is analyzed statistically using the one-way ANOVA test. The research result shows that giving 0.26 mg/kg of weight of deltamethrin and 0.26 mg/kg of weight of cypermethrin does not affect the increase in body weight, relative weight of the reproductive organ, and the level of intratesticular testosterone of male Wistar strain rats.